Three dimensional computational fluid dynamic interaction between soil and plowbreast of horizontally reversal plow - Zhu, Lin; Cheng, Xi; Peng, Shuang-Shuang; Qi, Yin-Yin; Zhang, Wen-Feng; Jiang, Rui; Yin, Cheng-Long (Computers and electronics in agriculture, 2016)
•3D Computational Fluid Dynamic modeling of the real mouldboard plough was proposed.•The pressure distributions on the plough-breast were obtained under various operation conditions.•CFD based analysis is feasibly and effectively used for in-depth study of soil-HRP interaction. Horizontally Reversible Plough (HRP) is more widely used than regular mouldboard ploughs due to excellent operation performances, e.g., commuting tillage and high tool speed. However, soil pressures over the plough surface in the HRP high-speed tillage process generally have adverse effects on the plough-breast and hence shorten the tool service life. In order to improve the plough-breast of HRP, this study proposed a new 3D Computational Fluid Dynamics (CFD) approach to investigate the real interaction between plough-breast and soil. For this purpose, first, the three dimensional model of the plough-breast was constructed in a commercial software SolidWorks; then, the soil from Xinjiang of China was chosen and characterized as a Bingham material according to the rheological behaviors; finally, 3D CFD predictions were implemented by the control volume method in a commercial code Fluent 6.2, addressing the soil pressures over the plough-breast surface under different tillage velocities, i.e., 5–8km/h and operation depths, i.e., 0.27–0.36m, respectively. The prediction results compared with the preliminary measured evidences and the previous FE models at the same settings with good agreement. This paper demonstrates feasibility and effectiveness of CFD based dynamic modeling to have great potential for in-depth study of soil-tool interaction by simulating realistic soil manners.